Diagnostic utility of colonoscopy and histological evaluation in the study of patients with chronic diarrhea - Nuñez Renza, Jesus Enrique (2021)
Introduction: Patients with chronic diarrhea often undergo colonoscopy evaluation, however, the performance of biopsies or ileoscopy remains controversial. Objective: To evaluate the usefulness of colonoscopy plus biopsies in the study of patients with chronic diarrhea. Materials and methods: We retrospectively reviewed patients with chronic diarrhea who underwent colonoscopy between 2015 and 2019. Patients with incomplete data, HIV infection, abnormal endoscopic findings, colonoscopy without blind assessment, being on empiric treatment for diarrhea, and poor diagnosis were excluded. preparation. A descriptive analysis of the characteristics of the patients, histopathological findings and comparison of signs and symptoms according to histopathological finding was performed. Results: 535 patients with chronic diarrhea were evaluated, of these, 283 (52.8%) underwent biopsies. In 55.1% (n=156) of the biopsies some final histopathological diagnosis was obtained. Histopathological diagnoses corresponded to ulcerative colitis (n=3), Crohn's disease (n=5), lymphocytic colitis (n=6), collagenous colitis (n=12), eosinophilic colitis (n=13), infectious colitis (n=13), Melanosis coli (n=15), nonspecific colitis (n=57) and other histological changes (n=32). Crohn's disease was only documented in biopsies of the ileum (p<0.001), ulcerative colitis was only diagnosed in biopsies of the sigmoid rectum (p=0.007), infectious colitis in its highest proportion (30.7%) was documented in biopsies of the right colon (p=0.028). Conclusion: Colonoscopy and biopsies are useful in the investigation of patients with chronic diarrhea, obtaining a histological diagnosis in 55% of patients. Ileoscopy complemented colonoscopy findings to a lesser extent.